Tingkat Belanja Online Flash Sale Di Kalangan Guru MTsN 11 Pesisir Selatan Analisis Etika Bisnis Islam - Efendi, Faisal (ITB AAS INDONESIA Surakarta, 2024)
The purpose of this study was to determine the level of online shopping among teachers at MTsN 11 Pesisir Selatan. Online shopping has become a habit or necessity for MTSN 11 Pesisir Selatan teachers. As was obtained from the Principal of MTSN 11 Pesisir Selatan, he said that almost every day online package delivery couriers come to the school. Therefore the author wants to examine how the level of online shopping for MTSN 11 Pesisir Selatan teachers. This study uses a quantitative descriptive method by explaining the data in the form of numbers into information. The object of this research is the teachers of MTSN 11 Pesisir Selatan from various levels. The data collection technique was by distributing questionnaires via Google form with a total of 65 respondents consisting of PNS, Honorary, and First Aid Teachers, Administrative Employees. Data were taken from July to early August 2023. The analytical tool used in this study used Microsoft Excel by distributing questionnaires via Google form to 65 respondents. The results of this study are that teachers often shop online at Shopee and Tiktok Shop stores by buying products in the Fashion category such as clothes, bags, shoes and others. Besides that, they also bought skincare and makeup. The principles of business ethics are in line and in harmony with the principles of Islamic business ethics.